RNAi‐mediated suppression of vimentin or glial fibrillary acidic protein prevents the establishment of Müller glial cell hypertrophy in progressive retinal degeneration. Issue 9 (24th May 2021) - Hippert, Claire; Graca, Anna B.; Basche, Mark; Kalargyrou, Aikaterini A.; Georgiadis, Anastasios; Ribeiro, Joana; Matsuyama, Ayako; Aghaizu, Nozie; Bainbridge, James W.; Smith, Alexander J.; Ali, Robin R.; Pearson, Rachael A.
Abstract: Gliosis is a complex process comprising upregulation of intermediate filament (IF) proteins, particularly glial fibrillary acidic protein (GFAP) and vimentin, changes in glial cell morphology (hypertrophy) and increased deposition of inhibitory extracellular matrix molecules. Gliosis is common to numerous pathologies and can have deleterious effects on tissue function and regeneration. The role of IFs in gliosis is controversial, but a key hypothesized function is the stabilization of glial cell hypertrophy. Here, we developed RNAi approaches to examine the role of GFAP and vimentin in vivo in a murine model of inherited retinal degeneration, the Rhodopsin knockout ( Rho −/− ) mouse. Specifically, we sought to examine the role of these IFs in the establishment of Müller glial hypertrophy during progressive degeneration, as opposed to (more commonly assessed) acute injury. Prevention of Gfap upregulation had a significant effect on the morphology of reactive Müller glia cells in vivo and, more strikingly, the reduction of Vimentin expression almost completely prevented these cells from undergoing degeneration‐associated hypertrophy. Moreover, and in contrast to studies in knockout mice, simultaneous suppression of both GFAP and vimentin expression led to severe changes in the cytoarchitecture of the retina, in both diseased and wild‐type eyes. These data demonstrate a crucial role for Vimentin, as well as GFAP, in the establishment of glial hypertrophy and support the further exploration of RNAi‐mediated knockdown of vimentin as a potential therapeutic approach for modulating scar formation in the degenerating retina. Main Points: Upregulation of Vimentin and GFAP can be suppressed in vivo using RNAi. Knockdown of vimentin or GFAP prevents Müller glial hypertrophy in the degenerating retina. Hypertrophy is not reversed by knockdown of either vimentin of GFAP once established.